OPTIMIZATION OF CONSERVATIVE TREATMENT OF REVIVING UTERINE BLEEDING OF PUBERTY - Khodjaeva A.S; Abdullazhanova S.A (Scholar Express Journals, 2024)
This article focuses on optimizing conservative therapy for menstrual bleeding in adolescent girls, with an emphasis on recurrent cases
Keywords: Uterine bleeding of puberty; recurrent bleeding